Swirling performance of flow-driven rotating mixing vane toward critical heat flux enhancement. (October 2015) - Seo, Han; Park, Seong Dae; Seo, Seok Bin; Heo, Hyo; Bang, In Cheol
Highlights: An innovative swirl generator, called moving rotational vane, was compared to conventional mixing vanes. Moving rotational vane showed the highest swirling performance compared to other vanes. Moving rotational vane could provide enhanced heat transfer and critical heat flux performance. Abstract: This paper presents experimental swirl generation measurements using a flow-driven rotating vane for heat transfer and critical heat flux enhancement in subchannels. In nuclear power plants, there are swirl generators, which are located on the top of the structural grids in the fuel assemblies. The mixing vanes are fixed on the spacer grids, thus there would be a limit for enhancing heat transfer performance because of the fixed positions. An innovative swirl generator, called moving rotational vane, was used to enhance heat transfer performance as well as critical heat flux by maximizing centrifugal force due to the swirl flow on the spacer grid. The experiments were conducted in vertical and horizontal flow experimental facilities using three types of vanes: (1) spacer grid (SG), (2) fixed split vane (FSV), and (3) moving rotational vane (MRV). Particle image velocimetry was applied to visualize the flow characteristics along the test sections; averaged velocity fields, averaged velocity vector components u and v, lateral and longitudinal flow distributions, turbulence intensities, and swirl ratio were analyzed. Computational fluid dynamics analysis was performed to show the effect of swirl generation and an air bubble injection experiment was conducted to show the effect of using the MRV. The pressure drop observed from the experiment using the SG, FSV, and MRV was 0.85, 1.97 and 2.59 kPa, respectively. On the other hand, in the CFD analysis, the pressure drop of the SG, FSV, and MRV was 1.86, 1.95, and 2.01 kPa at the same measurement length of the experiment, respectively. Swirl ratio was analyzed for the FSV and MRV. The swirl ratio of the MRV showed higher value compared to the FSV including conventional fixed split vanes. The analysis showed that the MRV induced the most powerful swirl generation. The MRV could provide secondary flow structures such as mixing and turbulence; thus, enhanced heat transfer as well as critical heat flux performance could be expected.